Peningkatan Hasil Belajar Teks Laporan Hasil Observasi Melalui Metode Pembelajaran Active Knowledge Sharing Resitasi Kelas X-8 SMAN 9 Surabaya - Lailatul Magfiroh (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
Through the use of repetition and the Active Knowledge Sharing learning approach, this study seeks to improve the learning outcomes of students in class X-8 SMAN 9 Surabaya when writing Observation Report Texts (LHO). Action research in the classroom was the methodology, and data was analyzed twice. The four phases of each cycle planning, action, observation, and reflection were designed to assess how well the applied learning approach worked. While learning outcomes were not at their best in the first cycle, there was an increase in students' active participation. All pupils attained learning completion after showing growth in the second cycle. This enhancement demonstrates that the Active Knowledge Sharing and recitation approach combination not only enhances students' engagement in the learning process but also significantly boosts their academic performance. Hence, this approach demonstrated efficacy in enhancing the caliber of education and pupils' learning results when composing Observation Report Texts.